Heat Treatment Effect on Eu3+ Doped TeO2-BaO-Bi2O3 Glass Systems with Ag Nanoparticles. (30th October 2017) - Lewandowski, Tomasz; Dembski, Michał; Walas, Michalina; Łapiński, Marcin; Narajczyk, Magdalena; Sadowski, Wojciech; Kościelska, Barbara
Abstract : Glass systems of 73TeO2 -4BaO-3Bi2 O3 -2Eu2 O3 - x Ag (in molar ratio where x = 0, 1, 2, and 3) compositions have been successfully synthesized. Silver nanoparticles were obtained with the employment of heat treatment (HT) procedure executed at 350°C. Glass transition temperatures of different compositions have been determined through DSC measurements. XRD results presented characteristic amorphous halo indicating lack of long range order in the samples. FTIR structural studies revealed that glass matrix is mainly composed of TeO3 and TeO4 species and is stable after different applied heat treatment times. X-ray photoelectron spectroscopy (XPS) measurements confirmed that in selected samples part of Ag ions changed oxidation state to form Ag 0 species. TEM measurements revealed nanoparticles of size in the range of 20–40 nm. UV-vis absorption results demonstrated characteristic transitions of Eu 3+ ions. Additionally, UV-vis spectra of samples heat-treated for 6, 12, 24, and 48 hours presented bands related to silver nanoparticles. Photoluminescence (PL) studies have been performed with excitation wavelength of λ e x c = 395 nm. Obtained spectra exhibited peaks due to 5 D0 - 7 F J (where J = 2, 3, 4 ) and 5 D1 - 7 F J (where J = 1, 2, 3 ) transitions of Eu 3+ . Moreover, luminescence measurement indicated enhancement of rare earth ions emissions in several of the annealed samples. Increase of emission intensity of about 35% has been observed.